Quality of life after electroconvulsive therapy in persons with treatment resistant schizophrenia - Garg, Rohit (Medknow Publications, 2011)
BACKGROUND & OBJECTIVES: In recent years, health-related quality of life (QOL) has been regarded as the most important dimension of outcome in schizophrenia. Recent research has shown that atypical antipsychotics improve QOL in patients with schizophrenia. Importance of electroconvulsive therapy (ECT) has been demonstrated in restoring function and health related quality of life in depressed patients. However, there are no data on patients of schizophrenia. The objective of the present study was therefore, to assess the improvement in quality of life after ECT in treatment resistant schizophrenia. METHODS: Thirty consecutive patients of treatment resistant schizophrenia were given ECT sessions twice a week and assessments were made with Positive and Negative Syndrome Scale of Schizophrenia (PANSS), WHO QOL Bref, Global Assessment of Functioning Scale and Clinical Global Impressions. RESULTS: The group improved significantly on all the domains of quality of life scale except the domain named satisfaction with social relations. There was also significant change in the total score of PANSS after 6 ECT sessions (mean at baseline = 86.7, mean after 6 ECT = 65.5, P< 0.001) as well as on different subscales of PANSS. The score on the global assessment of functioning also changed significantly (mean 26.3 at baseline to 44.5 after 6 ECT sessions). INTERPRETATION & CONCLUSIONS: The present findings showed that ECT in addition to improvement in symptomatology led to improvement in QOL in patients of treatment resistant schizophrenia.